2017
DOI: 10.5812/ijp.9727
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Calprotectin as a Marker to Distinguish Functional and Structural Acute Kidney Injury in Pediatric Population

Abstract: Background: Acute kidney injury (AKI) is a serious, common and occasionally under-recognized condition. To date, the clinical and some laboratory parameters are routinely applied to distinguish between functional and structural AKI which can be challenging in certain occasions. In the present paper, we investigate the accuracy of urinary calprotectin as a diagnostic biomarker in this dubious situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…[ 2 9 10 11 12 13 14 ] Detecting calprotectin in urine before its detection or its elevation in serum is much more helpful in clinical practice. [ 15 ] In gastrointestinal problems, fecal calprotectin level differentiate between inflammatory bowel disease from functional intestinal problems as this marker is raised only in inflammatory intestinal problems. Therefore, we planned to use urinary calprotectin in comparison with serum BUN and creatinine and GFR to detect its sensitivity and specificity in detecting early stages of AKI in children admitted in our PICU unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 2 9 10 11 12 13 14 ] Detecting calprotectin in urine before its detection or its elevation in serum is much more helpful in clinical practice. [ 15 ] In gastrointestinal problems, fecal calprotectin level differentiate between inflammatory bowel disease from functional intestinal problems as this marker is raised only in inflammatory intestinal problems. Therefore, we planned to use urinary calprotectin in comparison with serum BUN and creatinine and GFR to detect its sensitivity and specificity in detecting early stages of AKI in children admitted in our PICU unit.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies focused on the value of calprotectin in the differentiation of prerenal from intrinsic AKI. [ 15 ] In 2011, Heller et al . performed such a study and resulted that calprotectin has a high diagnostic value in intrinsic AKI and at a 300 ng/mL level has 92.3% sensitivity and 97.1% specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that urine calprotectin in renal group was higher than pre renal and calprotectin level correlated with severity of renal failure. Hence, Calprotectin with cut off value of 230 ng/ml with 95.6% sensitivity and 100% specificity can use to differentiate renal from prerenal AKI [3]. Seibert et al in 2016 assessed the power of calprotectin in differentiation of pre-renal and renal acute allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Acute renal failure is a common morbidity in neonates who are admitted in neonatal intensive care units (30% worldwide) [1]. Mortality and hospital stay lengths in neonates with AKI is higher than those without AKI [2] and the risk of chronic renal failure in adulthood increased in pediatrics with AKI [3]. It is obvious that prognosis of AKI is highly depended on early diagnosis and onset of treatment.…”
Section: Introductionmentioning
confidence: 99%